‘The Mkuze River it has crossed the fence’ (1) – communities on the boundary of the Mkuze protected area - Burgoyne, Christopher N.; Kelso, Clare J. (Bulletin of Geography. Socio-economic Series, 2014)
Restricting access to wilderness and wildlife resources is a contested topic in a time when developing nations are seeking to increase quality of life for their citizens. A case in point is the Mkuze Game Reserve which encompasses rich biodiversity and is surrounded by under-resourced rural communities. A history of exclusion from land and resources has left local residents feeling negative about western conservation ideals. Perceptions of protected areas and conservation objectives are important if management authorities are to affect a meaningful buy-in to conservation and sustainable resource use among local residents. In this paper, part of a larger mixed-methods study, we set out to explore the perceptions three rural communities have of 1) local land-cover and livelihood change and 2) the socio-economic benefits expected and derived from living adjacent to Mkuze Game Reserve, a publicly administered protected area in KwaZulu-Natal, South Africa. People living around the reserve felt they receive few benefits from living near to a protected area. Management countered that they are not well funded enough to provide much development support. In addition to this, the community sees a contrast between this lack of benefit sharing and the successful benefit sharing experienced by a neighbouring community which borders a private reserve. This has added to their negative view of the way Mkuze Game Reserve management has been engaging with communities. Effective engagement with communities and understanding their expectations will be important for strengthening conservation initiatives and community engagement objectives in the area.